Design of e-Samsat Services at The West Java Regional Revenue Agency (Case Study of Bandung City) - Triesna Priastuti; Asep Sumaryana; Sawitri Budi Utami (Universitas Padjadjaran, 2022)
Motor vehicle tax payment services (PKB) organized by West Java Regional Revenue Agency follow the development of information and communication technology. West Java Regional Revenue Agency is required to adjust the design of services in order to provide convenience to the community, both in terms of time and cost. In carrying out motor vehicle tax payment services, in this case it is more interesting to study because the City of Bandung contributes high tax revenue for motor vehicles in West Java Province. West Java Regional Revenue Agency is supported by the Center of Operational Services of Regional Revenue (PLOPD), The Bandung I Pajajaran Office of Regional Revenue, The Bandung II Kawaluyaan Office of Regional Revenue and The Bandung III Soekarno Hatta Office of Regional Revenue in providing e-Samsat public services in Bandung. The purpose of this study is to describe the design of e-Samsat services in the city of Bandung. Qualitative research methods were used in this research where information was obtained from 34 informants who were then triangulated by the author. Observations were made at all Samsat service locations in the city of Bandung. The results showed that the design of the e-Samsat service by West Java Regional Revenue Agency (Case Study of Bandung City) had applied information and communication technology through the SAMBARA application which was supported by banking services, e-commerce and modern outlets.